2011
DOI: 10.1371/journal.ppat.1002281
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Efficient Clearance of Blood-borne Virus by Liver Sinusoidal Endothelium

Abstract: The liver removes quickly the great bulk of virus circulating in blood, leaving only a small fraction to infect the host, in a manner characteristic of each virus. The scavenger cells of the liver sinusoids are implicated, but the mechanism is entirely unknown. Here we show, borrowing a mouse model of adenovirus clearance, that nearly all infused adenovirus is cleared by the liver sinusoidal endothelial cell (LSEC). Using refined immunofluorescence microscopy techniques for distinguishing macrophages and endot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
150
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(159 citation statements)
references
References 25 publications
9
150
0
Order By: Relevance
“…3), prompted us to examine the transduction efficiency of NiVpp in vivo, especially when NiVpp were administered intravenously and therefore subjected not only to dilution into the blood and tissue volume but also to the problem of hepatic clearance, a critical barrier for in vivo virusbased gene therapy (23,24,62). Interestingly, when VSVpp and NiVpp carrying a luciferase reporter gene were injected intravenously into mice and subsequently subjected to whole-animal and -organ imaging for D-luciferin-induced bioluminescence signals, T5F⌬N3/wt G NiVpp demonstrated an enhanced signal in the spleen and lungs compared to T5F/wt G NiVpp (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3), prompted us to examine the transduction efficiency of NiVpp in vivo, especially when NiVpp were administered intravenously and therefore subjected not only to dilution into the blood and tissue volume but also to the problem of hepatic clearance, a critical barrier for in vivo virusbased gene therapy (23,24,62). Interestingly, when VSVpp and NiVpp carrying a luciferase reporter gene were injected intravenously into mice and subsequently subjected to whole-animal and -organ imaging for D-luciferin-induced bioluminescence signals, T5F⌬N3/wt G NiVpp demonstrated an enhanced signal in the spleen and lungs compared to T5F/wt G NiVpp (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Biodistribution studies quantifying genome-integrated vector copy numbers in various tissues confirmed these observations. Bypassing the liver sink is a critical barrier for targeted gene therapy (23,24), suggesting that the extraordinary specificity of NiV-G for ephrinB2 may allow for targeting of specific ephrinB2 ϩ populations in vivo or in vitro, without the need for prior cell purification.…”
mentioning
confidence: 99%
“…The systemic delivery route for gene delivery vehicles is very promising, but has major caveats. On the one hand, the vasculature has the potential to be a conduit to the entire CNS (every cell in the brain is a maximum distance of 40 μm from an endothelial cell [22]), while on the other hand the BBB blocks transport of most delivery vehicles (see section below on Blood-Brain Barrier), and the filtration systems of the spleen and liver are efficient at removal of viruses and virus vectors from the circulation before they can reach the brain [23][24][25][26]. Other non-target organs, such as muscle and heart, will also be transduced with potential off-target toxicities.…”
Section: Delivery Route and Gene Transfer Efficiency To Target And Nomentioning
confidence: 99%
“…Expression of the C-type lectin L-SIGN by LSECs was postulated to mediate capture of HCV particles and transcytosis of the virus across the endothelial barrier, thereby concentrating infectious particles and facilitating their direct contact with hepatocytes (102). Moreover, LSECs are highly efficient scavengers that pinocytose particles less than 0.2 μm in size, which typically encompasses virus-sized particles (103). The recent demonstration that LSECs, rather than KCs, clear the bulk of blood-borne human adenovirus underscores their importance during the viremic phase of any natural viral infection (103).…”
Section: Figurementioning
confidence: 99%
“…Moreover, LSECs are highly efficient scavengers that pinocytose particles less than 0.2 μm in size, which typically encompasses virus-sized particles (103). The recent demonstration that LSECs, rather than KCs, clear the bulk of blood-borne human adenovirus underscores their importance during the viremic phase of any natural viral infection (103). Even if LSECs do not sustain active replication, viral sensing and its downstream effector responses, including exosomal transfer of ISG products (ref.…”
Section: Figurementioning
confidence: 99%